Exploring the Potentials of Lysinibacillus sphaericus ZA9 for Plant Growth Promotion and Biocontrol Activities against Phytopathogenic Fungi - Naureen, Zakira; Rehman, Najeeb Ur; Hussain, Hidayat; Hussain, Javid; Gilani, Syed A.; Al Housni, Saif K.; Mabood, Fazal; Khan, Abdul L.; Farooq, Saima; Abbas, Ghulam; Harrasi, Ahmed A. (Frontiers in Microbiology, 2017)
There is an ongoing hunt for biologically-active compounds that can combat phytopathogenic fungi and improve plant growth without causing any hazards to the environment. Consequently the present study aims at deciphering the plant growth promotion and antifungal capability of Lysinibacilluys sphaericus ZA9. The bacterium was previously isolated and identified in our laboratory from maize rhizosphere using 16S rRNA gene sequencing. The test bacterium Lysinibacillus sphaericus ZA9 was found to produce high quantity of IAA (697 µg/ mL); siderophores (195.79 µg/ mL), HCN and hydrolytic enzyme as compared to the reference strain Bacillus sphaericus Z2-7. The bacterium was also capable of solubilizing silicates (Si), phosphates (P) and potassium (K). The bacterium enhanced the seedling vigour and germination of seeds pretreated with it and promoted the shoot length of both cucumber and tomato seeds in greenhouse experiment. Lysinibacillus sphaericus ZA9 and its cell free culture supernatant (CFCS) showed varied antaganoistic behaviour against Alternaria alternata, Curvularia lunata, Aspergillus sp., Sclerotinia sp., Bipolaris spicifera, Trichophyton sp. Fermentation broth culture of Lysinibacillus sphaericus ZA9 was then used to isolate antifungal metabolites by silica column chromatography. Identification and determination of antifungal compounds was carried out by Thin-layer chromatography (TLC) followed by NMR spectroscopy. Two compounds were isolated and identified as 2-pentyl-4-quinolinecarboxylic acid (C15H17NO2) which is a quinoline alkaloid and 1- methylcyclohexene which is a cycloalkene. Compound 1; 2-Penthyl-4-quinolinecarboxylic acid was found to be highly antagonistic against most of the fungi tested as compared to the bacterium itself. Its activity was comparable to that of fungicide Benlate , while compound 2; 1- methylcyclohexene did not show any antifungal activity.